Experimental and numerical study of supercapacitors module with air-cooling. (August 2019) - Voicu, Ionut; Rizk, Rania; Louahlia, Hasna; Bode, Florin; Gualous, Hamid
Highlights: The thermal management of staggered supercapacitor stack is studied. The surface temperatures are measured for natural and forced convection. The numerical model enables to predict the temperature field for forced convection. The thermal behaviour of the module operating at high current rates is investigated. The risk of overheating is predicted for steady state and transient regime. Abstract: This paper deals with the thermal management of a supercapacitor module with air-cooling. An experimental test bench is used for thermal characterization of nine supercapacitors assembled in a module with a staggered arrangement by measuring surface temperatures for several current rates (up to 70 A) and inlet air velocities between zero and 0.6 m s −1 . The experimental results obtained in natural convection make it possible to estimate the maximal relative surface temperature at 84 A (the maximum current rate) between 26.6 °C and 30 °C. This result shows that overheating can occur for high current rates and air temperature higher than 30 °C, so a ventilation cooling system can be useful. A numerical study is also undertaken for forced convection regime (inlet airflow between 0.2 m s −1 and 0.8 m s −1 ) and 70 A current rate. The numerical results are in good agreement with the experimental results. The mean deviation between experimental and numerical relative temperatures is 19.8% for steady state regime and 17.5% for transient regime comparison. Therefore, numerical simulations are used to estimate the temperature distribution within the supercapacitors. At steady state regime, the difference between maximal internal temperature and maximal surface temperature is between 2.5 °C and 3 °C. At steady state regime, the maximum temperature is located near the axis and for transient regime, it is located inside the active zone. The evolution of temperatures for maximal current rate and 40 °C inlet air temperature is also studied numerically. Overheating can occur for steady state regime for a velocity less than 0.15 m s −1 . On the other hand, after four minutes' work the temperature of supercapacitors remains lower than 42.5 °C and is very slightly influenced by the velocity of air.